2017
DOI: 10.3892/etm.2017.4858
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical trial of the multi-targeted lenvatinib in combination with cellular immunotherapy for treatment of renal cell carcinoma

Abstract: Abstract. Lenvatinib is an oral, multi-targeted tyrosine kinase inhibitor of vascular endothelial growth factor receptors 1-3, fibroblast growth factor receptors 1-4, platelet-derived growth factor receptor β, RET and KIT. Cellular immunotherapy has the potential to be a highly targeted treatment, with low toxicity to normal tissues and a high capacity to eradicate tumor tissue. The present study assessed the safety, maximum tolerated dose (MTD) and preliminary antitumor activity of lenvatinib and cellular imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…In addition, regulatory T cells express VEGFR-2, and stimulation through VEGF-A is connected with PD-1 increase and inhibition of T cells 30. A preclinical study in renal cell carcinoma (RCC) demonstrated that cellular immunotherapy in association with lenvatinib significantly increases survival in murine models; 31 furthermore, the association of lenvatinib and pembrolizumab has shown efficacy in a phase I study, particularly in RCC and melanoma,32 with a high disease-control rate.…”
Section: Modulation Of Immune Cells and Tumor Microenvironment By Lenmentioning
confidence: 99%
“…In addition, regulatory T cells express VEGFR-2, and stimulation through VEGF-A is connected with PD-1 increase and inhibition of T cells 30. A preclinical study in renal cell carcinoma (RCC) demonstrated that cellular immunotherapy in association with lenvatinib significantly increases survival in murine models; 31 furthermore, the association of lenvatinib and pembrolizumab has shown efficacy in a phase I study, particularly in RCC and melanoma,32 with a high disease-control rate.…”
Section: Modulation Of Immune Cells and Tumor Microenvironment By Lenmentioning
confidence: 99%